INDICATORS OF LABOR EFFICIENCY (Лучшие интеллектуальные исследования, 2025)
Annotation. This article analyzes the indicators of labor efficiency and their role in economic development. Labor efficiency, at the level of organization and countries, reflects the level of resource use of the labor force. The article discusses the main indicators used in the assessment of labor efficiency, including factors such as the volume of production, the level of wages and the efficiency of working hours. Opinions are also expressed on innovative approaches, modern technologies and skill development programs necessary to improve labor efficiency. On the example of Uzbekistan, practical methods of improving labor efficiency and the impact of this process on economic stability are considered. The article also highlights the importance of cooperation between the public and private sectors in improving labor efficiency and outlines future development prospects.